Hydrodynamic dispersion drives viral–cellular contact for gene delivery in porous media - Vishal Srikanth; Micah Mallory; Andrew J. Ulmer; Wesley R. Legant; Andrey V. Kuznetsov; Yevgeny Brudno (Proceedings of the National Academy of Sciences, 2026)
Reactive biological processes often hinge on rare collisions between particles whose transport is governed by disparate advective, diffusive, and sedimentary mechanisms. Biological cell–virus encounters offer a uniquely quantifiable instance of this general problem: collisions between particles whose transport is governed by entirely different physical mechanisms, yet whose interactions determine system-level function. In stagnant liquids, nanoscale viral vectors explore space only via slow Brownian diffusion, whereas microscale cells rapidly sediment, producing species separation that suppresses virus-cell interfacial interactions. Here we show that liquid absorption into a dry, macroporous sponge enhances viral–cellular interactions by shifting the system into an advection-dispersion regime that circumvents this sedimentation-diffusion limit. By integrating experimental results with a multiscale simulation model, we demonstrate that the tortuous sponge porosity converts capillary-driven flow into convective mixing, driving orders-of-magnitude increases in viral–cellular collision rates. Coupling these dispersive transport dynamics with a probabilistic capture model reveals that hydrodynamic dispersion accounts for the multifold enhancement in viral–cellular transduction efficiency observed in porous sponges. These results provide a quantitative framework for emergent collision dynamics in complex porous media and establish a generalizable strategy to optimize active transport in spatiotemporally heterogeneous biological systems.